Natural compounds as potential adjuvants to cancer therapy: Preclinical evidence - Lin, Shian‐Ren; Chang, Chia‐Hsiang; Hsu, Che‐Fang; Tsai, May‐Jwan; Cheng, Henrich; Leong, Max K.; Sung, Ping‐Jyun; Chen, Jian‐Chyi; Weng, Ching‐Feng (British journal of pharmacology, 2020)
Traditional chemotherapy is being considered due to hindrances caused by systemic toxicity. Currently, the administration of multiple chemotherapeutic drugs with different biochemical/molecular targets, known as combination chemotherapy, has attained numerous benefits like efficacy enhancement and amelioration of adverse effects that has been broadly applied to various cancer types. Additionally, seeking natural‐based alternatives with less toxicity has become more important. Experimental evidence suggests that herbal extracts such as Solanum nigrum and Claviceps purpurea and isolated herbal compounds (e.g., curcumin, resveratrol, and matairesinol) combined with antitumoral drugs have the potential to attenuate resistance against cancer therapy and to exert chemoprotective actions. Plant products are not free of risks: Herb adverse effects, including herb–drug interactions, should be carefully considered. Linked Articles This article is part of a themed section on The Pharmacology of Nutraceuticals. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.6/issuetoc